Kedudukan Sidik Jari dalam Proses Penyidikan Tindak Pidana di Kepolisian Resor Gorontalo Perspektif Hukum Islam - Noor Asma; Farhan Nikson Taha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
Fingerprints are evidence that can be categorized as evidence of letters and expert statements, even as complementary and supporting evidence in carrying out the investigation process to reveal the perpetrators of criminal acts. The purpose of the article is to examine the position of fingerprints as evidence in the process of investigating criminal acts in Islamic law. In answering these problems, the author uses a qualitative approach, and empirical normative research methods, namely research that uses empirical normative legal case studies of legal behavior products. The results of the research show that in the cases handled by the Gorontalo Resort Police, the accuracy rate reaches 90 percent in collecting evidence and revealing the perpetrators of criminal acts through fingerprint identities. So that the position of fingerprints in identifying victims and perpetrators of criminal acts is very important to uncover and scientifically prove victims and perpetrators, which can be categorized as evidence of expert testimony that provides information from the identification results. The legal consequences that can be caused to perpetrators or defendants who have wrong identities due to incorrectly identifying fingerprints during investigations and investigations in the trial process are charges that are null and void based on article 143 paragraph 3 of the Criminal Procedure Code. Evidence using fingerprints in Islamic law is not directly stated in the evidence, but Islamic law is dynamic according to place and time so that fingerprint evidence can be verified with evidence of instructions (qarinah).